2011
DOI: 10.1525/cond.2011.090200
|View full text |Cite
|
Sign up to set email alerts
|

Winter Distribution of Willow Flycatcher Subspecies

Abstract: Documenting how different regions across a species' breeding and nonbreeding range are linked via migratory movements is the first step in understanding how events in one region can influence events in others and is critical to identifying conservation threats throughout a migratory animal's annual cycle. We combined two studies that evaluated migratory connectivity in the Willow Flycatcher (Empidonax traillii), one using mitochondrial DNA sequences from 172 flycatchers sampled throughout their winter range, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…However, to explain our toe-pad sequence data would require an extremely high level of unidirectional hybridization. One would expect similar levels of sequence mismatch in samples of E. traillii, which Paxton et al (2011) did not report. Surveys of nuclear loci could determine the frequency of hybridization, but it is not likely high enough to explain why so many E. alnorum were identified as E. traillii.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, to explain our toe-pad sequence data would require an extremely high level of unidirectional hybridization. One would expect similar levels of sequence mismatch in samples of E. traillii, which Paxton et al (2011) did not report. Surveys of nuclear loci could determine the frequency of hybridization, but it is not likely high enough to explain why so many E. alnorum were identified as E. traillii.…”
Section: Discussionmentioning
confidence: 80%
“…Because field collectors had not searched consistently over the migration periods for Empidonax, we do not list extreme or median dates of passage. Paxton et al (2011) found E. traillii to be common migrants along the west coast of Mexico and Central America, suggesting that these two sibling species have different principal migration routes through the Isthmus of Tehuantepec in spring and fall.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, a number of migratory species are experiencing higher population declines than resident birds (Sanderson et al 2006, Sauer andLink 2011), suggesting for some species that the cost of migration may be overwhelming potential benefits. However, to determine the ecological drivers that shape mortality throughout the annual cycle more studies ground study was within the core range of the southwestern subspecies, at two of the largest known breeding sites, and analysis of molecular genetics and morphology both indicate strong connectivity between the southwestern subspecies and the Pacific lowlands of Costa Rica where our wintering study was conducted (Paxton et al 2011). Despite the fact that the southwestern subspecies only constitutes approximately 0.2% of the estimated 3.2 million willow flycatchers (Rich et al 2004), and the species winters over a large area from central Mexico to South America, we documented direct linkage between our breeding and wintering study sites via 2 individuals banded in the southwestern subspecies' range that were recaptured in Costa Rica .…”
Section: Discussionmentioning
confidence: 99%
“…Zink [11] performed but did not show a phylogenetic analysis of 93 mtDNA Cytb haplotypes deposited in Genbank, but not analyzed by, E. Paxton. According to Paxton et al [27], these haplotypes came from breeding birds sampled in New York, Tennessee, Illinois, North Carolina, Virginia, North Dakota, South Dakota, Minnesota, and Maryland, Washington, Oregon, and California. The 93 Genbank haplotypes include those used by Paxton et al [26].…”
Section: Molecular Data and C-group Haplotypesmentioning
confidence: 99%